Migration patterns of subgenus Alnus in Europe since the last glacial maximum: a systematic review - Douda, Jan; Doudová, Jana; Drašnarová, Alena; Kuneš, Petr; Hadincová, Věroslava; Krak, Karol; Zákravský, Petr; Mandák, Bohumil (PLoS One, 2014)
BACKGROUND/AIMS: Recently, new palaeoecological records supported by molecular analyses and palaeodistributional modelling have provided more comprehensive insights into plant behaviour during the last Quaternary cycle. We reviewed the migration history of species of subgenus Alnus during the last 50,000 years in Europe with a focus on (1) a general revision of Alnus history since the Last Glacial Maximum (LGM), (2) evidence of northern refugia of Alnus populations during the LGM and (3) the specific history of Alnus in particular European regions. METHODOLOGY: We determined changes in Alnus distribution on the basis of 811 and 68 radiocarbon-dated pollen and macrofossil sites, respectively. We compiled data from the European Pollen Database, the Czech Quaternary Palynological Database, the Eurasian Macrofossil Database and additional literature. Pollen percentage thresholds indicating expansions or retreats were used to describe patterns of past Alnus occurrence. PRINCIPAL FINDINGS: An expansion of Alnus during the Late Glacial and early Holocene periods supports the presence of alders during the LGM in southern peninsulas and northerly areas in western Europe, the foothills of the Alps, the Carpathians and northeastern Europe. After glaciers withdrew, the ice-free area of Europe was likely colonized from several regional refugia; the deglaciated area of Scandinavia was likely colonized from a single refugium in northeastern Europe. In the more northerly parts of Europe, we found a scale-dependent pattern of Alnus expansion characterised by a synchronous increase of Alnus within individual regions, though with regional differences in the times of the expansion. In southern peninsulas, the Alps and the Carpathians, by contrast, it seems that Alnus expanded differently at individual sites rather than synchronously in whole regions. CONCLUSIONS: Our synthesis supports the idea that northern LGM populations were important sources of postglacial Alnus expansion. The delayed Alnus expansion apparent in some regions was likely a result of environmental limitations.
Keywords: Paleontology; olše; Europe; Evropa; Carbon Radioisotopes; radioizotopy uhlíku; Geography; Alnus; Demography; Pollen; paleontologie; pyl; zeměpis; demografie